2019
DOI: 10.24106/kefdergi.2752
|View full text |Cite
|
Sign up to set email alerts
|

Yatılı Bölge Ortaokulu Öğrencilerinin STEM Alanlarına Yönelik Kariyer Farkındalığının Araştırılması

Abstract: Bu araştırmada, yatılı bölge ortaokulu öğrencilerinin fen, teknoloji, mühendislik, matematik (STEM)) alanlarında kariyer geliştirmeye yönelik farkındalıkları, ilgileri ve bu ilgilerinin dayandığı unsurların belirlenmesi amaçlanmaktadır. Araştırmada karma yöntemler araştırma desenlerinden keşfedici ardışık desen kullanılmıştır. Araştırmanın çalışma grubunu yatılı bölge ortaokulunda (YBO) 8. sınıfta öğrenim gören 92 öğrenci oluşturmaktadır. Araştırmanın nitel verileri doküman (anket) ve odak grup görüşme yöntemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…As a result of the study, it was observed that students learned concepts about science and technology and they learned group discussion and building. Research focusing on the use of STEM activities for middle school students confirms similar results (Bozkurt-Altan et al, 2019;Kolodner, 2002;Sürmeli et al, 2018). Besides, from the results of the study, it is understood that students were able to relate to STEM areas and activities successfully.…”
Section: Discussionmentioning
confidence: 52%
“…As a result of the study, it was observed that students learned concepts about science and technology and they learned group discussion and building. Research focusing on the use of STEM activities for middle school students confirms similar results (Bozkurt-Altan et al, 2019;Kolodner, 2002;Sürmeli et al, 2018). Besides, from the results of the study, it is understood that students were able to relate to STEM areas and activities successfully.…”
Section: Discussionmentioning
confidence: 52%
“…Boarding regional secondary schools were established in order to meet the educational needs of poor family children who have reached compulsory education age in settlements where the population is small and scattered (MoNE, 2003). Additionally, studies revealing that RBS students have low awareness about career options in STEM fields (Bozkurt Altan, Üçüncüoğlu & Zileli, 2019) show that the present study will contribute to the field in this sense as well.…”
Section: Socio-economically Disadvantaged Groups Social Justice and mentioning
confidence: 63%
“…STEM eğitim yaklaşımının tamamen sınıf içinde uygulanmasında zorluklarla karşılaşılmış ve bu nedenle okul dışı STEM eğitimi de STEM eğitimini yaygınlaştırmak için kullanılmıştır (Akgündüz vd., 2015). Türkiye'de hem sınıf içi hem de okul dışında yapılan çalışmalar bulunmaktadır (Baran, Canbazoğlu Bilici, Mesutoğlu & Ocak, 2015;Bozkurt Altan, Üçüncüoğlu & Zileli, 2019;Gencer, 2015;Özcan & Koca, 2019;Şahin, Ayar & Adıgüzel, 2014;Yamak, Bulut & Dündar, 2014). STEM eğitim yaklaşımı kısa sürede dünyaya yayılarak, gelişmiş ve gelişmekte olan ülkelerin öğretim programlarında yerini almıştır.…”
unclassified